Religious Values in the Practice of Mutual Cooperation as a Manifestation of a Sakinah Family in Gayam Hamlet, Mojopuro, Wonogiri - Mardhiyyah Minda Marsay; Nasya Kamila Nayla Rasyid; Nasichah N (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Gotong royong, or mutual cooperation, is a local tradition that plays an essential role in strengthening social harmony and religious values within communities. This community service project aims to explore how the practice of gotong royong in RT 03 Dusun Gayam contributes to the development and preservation of the family sakinah values in the Islamic perspective. This study employed a qualitative approach through observation, interviews, and documentation during the implementation of Praktikum Profesi Makro. The results revealed that the spirit of gotong royong remains strong in various activities, including road construction, social support during communal events, and agricultural collaboration. These collective actions are based on the Islamic principle of ta’awun, which encourages mutual help as a form of worship and social responsibility. Moreover, the tradition serves as a medium for the intergenerational transmission of values such as unity, care, and collective responsibility. Thus, gotong royong in Dusun Gayam not only reinforces social cohesion but also serves as a practical implementation of family sakinah values in community life.